The Success Factors of Conversion Process Using ADKAR Model: A Case Study of Islamic Savings Loan and Financing Cooperative - Mukhamad Yasid; Sugiyarti Fatma Laela (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2022)
This study aims to analyse the conversion-related issues from Savings and Loan Cooperative (SLC) into Islamic Savings Loan and Financing Cooperative (ISLFC) using a case study of Tunas Artha Mandiri (TAM) Cooperative, located in Nganjuk, East Java. Five main research questions include: exploring reasons for conversion, explaining the conversion process, assessing the level of conversion effectiveness, identifying obstacles during the conversion and analysing key success factors of conversion. This study applied a mixed method. A qualitative method was applied to answer the first four questions and a quantitative method with a structural equation model was used to answer the fifth question. Using 120 members of TAM as our respondents, this study found that the success of conversion depends on the awareness of human resources to emigrate and the reinforcement to emigrate, especially from the founders. In addition, this awareness indirectly affects the success of conversion through desire, knowledge, ability and reinforcement. In order to succeed, the cooperative management should provide socialization on how to run ISLFC effectively as well as gradual training.